Current Status of Immunotherapy for Non-Small-Cell Lung Cancer. Issue 4 (July 2016) - Imbimbo, Martina; Lo Russo, Giuseppe; Blackhall, Fiona
In the last few years, the introduction of novel immunotherapeutic agents has represented a treatment shift for a subset of patients with non-small-cell lung cancer (NSCLC). Checkpoint inhibitors have been demonstrated to improve survival in advanced stage disease with very good tolerability. This success follows many years of scientific effort to manipulate the human immune system to attack cancer cells. With a variety of approaches ranging from vaccines to administration of interleukin or interferon-γ, the results in NSCLC were unsuccessful, with the view that it is a scarcely immunogenic cancer, unlike melanoma or renal cell carcinoma. The step change has come from understanding of immune checkpoints—cell surface molecules that regulate immune system activation and mediate coinhibitory signaling pathways that physiologically protect the body from autoimmunity. These pathways play an important role in tumors, including NSCLC, and are a mechanism of escape from immune surveillance. Several monoclonal antibodies have been developed in order to inhibit these molecules and unleash the brakes of the immune system. Currently in NSCLC, 7 different checkpoint inhibitors are under investigation: 2 anti-cytotoxic T-lymphocyte-associated antigen 4, 2 anti-programmed death (PD)-1, and 3 anti-PD-ligand 1 antibodies. Here we review the progress to date in developing immunotherapy for NSCLC, summarize results from published trials, highlight ongoing trials, and discuss progress in the question of how best to select patients for this treatment.